Star bound : a beginner's guide to the American space program, from Goddard's rockets to Goldilocks planets and everything in between - Carney, Emily; McCandless, Bruce, III (Outward odyssey., 2025)
"Star Bound is a book for anyone who wants to learn about the American space program but isn't sure where to start. First and foremost, it's a history-short, sweet, and straightforward. From rocketry pioneer Robert Goddard's primitive flight tests in 1926 through the creation of NASA, from our first steps on the moon to construction of the International Space Station and planning a trip to Mars, readers will meet the people and projects that have put the United States at the forefront of space exploration. Along the way, they'll learn: How the United States beat the Soviets to the moon Why astronauts float in space (Hint: It's not for lack of gravity!) How fast rockets have to go to stay in orbit around Earth How we can "look back in time" through a space telescope With technology evolving and humanity's understanding of the universe expanding, we are entering an exciting period of space exploration. Authored by two veteran space writers with unique insights into the topic, Star Bound offers up the story of Americans in space with a focus on the cultural and societal contexts of the country's most important missions rather than engineering and technical minutiae. Vibrant, positive, and humorous, Star Bound is packed with facts and stories for novice space fans. And sprinkled in with the history are lists of the greatest space songs, books, movies, and more-all designed to make space exploration accessible to even the casual reader"--